Manajemen Strategi dan Penjaminan Mutu untuk Pendidikan Berkelanjutan: Tinjauan Sistematis Literatur - Miftahul Jannah; Muhammad Eko Nurfaiz; Hikmah Kamila Salsabyla Az; Mu’alimin Mu’alimin (Jurnal Cakrawala Pendidikan dan Biologi, 2025)
The quality of education is a crucial issue that continues to receive attention in facing the challenges of globalization, digitalization, and the demands of 21st century competencies. Quality improvement efforts are not only related to the quality of students' learning outcomes, but also concern the role of leadership, management effectiveness, and the implementation of a quality assurance system. This study aims to identify strategies to improve the quality of education that have been studied in the literature for the last five years (2020-2025) and answer two research questions, namely: (1) what quality strategies are predominantly discussed in the literature, and (2) how the role of leadership, strategy management, and quality assurance in supporting the quality of education. The method used is literature review with a qualitative approach. Data was obtained from Google Scholar and Publish or Perish (PoP) databases using the keyword "quality strategy" with a publication year limit of 2020–2025. The search yielded 30 articles, which then through a screening and selection process obtained 5 relevant articles for analysis. The results of the analysis show three main trends: (1) the strategic role of school principals in building a quality culture, (2) the importance of evaluation and implementation of quality management in a sustainable manner, and (3) the synergy of visionary leadership with the quality assurance system as the basis for sustainable quality. This study concludes that the education quality strategy requires the integration of these three aspects. Going forward, further research is needed to develop integrative models across approaches and broader educational contexts.